Jesuit Schools and Universities in Europe, 1548-1773 Brill's Research Perspectives in Jesuit Studies - Grendler, Paul F. (Brill Research Perspectives in Humanities and Social Sciences, 2018)
A survey of Jesuit schools and universities across Europe from 1548 to 1773 by Paul F. Grendler. The article discusses organization, curriculum, pedagogy, enrollments, and relations with civil authorities with examples from France, Germany, Austria, Italy, Portugal, Spain, and eastern Europe.